The Electrochemical Properties of Sr(Ti, Fe)O3-δ for Anodes in Solid Oxide Fuel Cells. Issue 4 (1st January 2017) - Nenning, Andreas; Volgger, Lukas; Miller, Elizabeth; Mogni, Liliana V.; Barnett, Scott; Fleig, Jürgen
Abstract : Reduction-stable mixed ionic and electronic conductors such as Sr(Ti, Fe)O3-δ (STF) are promising materials for application in anodes of solid oxide fuel cells. The defect chemistry of STF and its properties as solid oxide fuel cell (SOFC) cathode have been studied thoroughly, while mechanistic investigations of its electrochemical properties as SOFC anode material are still scarce. In this study, thin film model electrodes of STF with 30% and 70% Fe content were investigated in H2 +H2 O atmosphere by electrochemical impedance spectroscopy. Lithographically patterned thin film Pt current collectors were applied on top or beneath the STF thin films to compensate for the low electronic conductivity under reducing conditions. Oxygen exchange resistances, electronic and ionic conductivities and chemical capacitances were quantified and discussed in a defect chemical model. Increasing Fe content increases the electro-catalytic activity of the STF surface as well as the electronic and ionic conductivity. Current collectors on top also increase the electrochemical activity due to a highly active Pt-atmosphere-STF triple phase boundary. Furthermore, the electrochemical activity depends decisively on the H2 :H2 O mixing ratio and the polarization. Fe 0 nanoparticles may evolve on the surface in hydrogen rich atmospheres and increase the hydrogen adsorption rate.